DEVELOPING A TEACHING BOOK ‘ENGLISH FOR MATH’ BASED ON LOCAL WISDOM - Siregar, Ayu Meita Puteri; Sahyoni, Sahyoni; Suadi, Suadi (Universitas Muhammadiyah Metro, 2025)
This study introduces an innovative approach to English for Specific Purposes (ESP) by developing an English for Mathematics textbook infused with local wisdom. This novel integration bridges the gap between linguistic competence and cultural relevance in mathematics education. Employing the Research and Development method, this work addresses a critical gap in ESP materials by embedding indigenous knowledge into mathematical English instruction, a unique contribution to the field. Participants from the Mathematics Education Study Program at STAIN Mandailing Natal provided insights through questionnaires, validation sheets, and interviews, with data analyzed using descriptive statistics. The findings reveal a strong student need for a textbook that integrates mathematical English vocabulary, communicative teaching methods, and skill-based tasks in speaking and reading. The integration of local wisdom enhances student engagement. It promotes culturally responsive learning, making the textbook distinct from standard ESP materials. Expert reviews affirmed its high quality in terms of content, design, and language. Student responses highlighted its practicality, interactivity, and creativity, reflecting its educational innovation. This study contributes to the global ESP field by demonstrating that localized content can enhance English skills in specific disciplines, providing a model adaptable to other contexts. The textbook emerges as a groundbreaking tool for culturally sustaining mathematics education.